(untitled) (World Economics and Finance Bulletin, 2022)
Attracting foreign direct investment (FDI) is an important pillar of economic development policy, and most countries in the world have established national investment promotion agencies (IPAs) with the mandate to attract FDI. The technical note highlights best practices in investment promotion and presents several innovative and in many ways replicable programs from around the world, which could fill the gaps in current investment promotion activities of IPAs in Latin America and the Caribbean. It outlines key implementation issues and serves as a practical policy guide for IPAs across the region to enhance their capability to attract and retain FDI